Budikdamber Training to Enhace Women’s Quality of Life through ABCD in Tegalsari Cirebon - Cory Vidiati; Kharimah Kharimah; Citra Lela; Yahya Huda Pratama; Nicha Rosalin (GUYUB: Journal of Community Engagement, 2024)
This service focuses on empowering housewives in Tegalsari Village, Plered District, Cirebon Regency, through the 2024 Community Service Lecture program of Universitas Islam Bunga Bangsa Cirebon (UIBBC). This program optimizes the Asset-Based Community Development (ABCD) approach to increase the economic independence of housewives through catfish cultivation and plants in buckets (budikdamber). The purpose of this service is to identify the potential and assets of housewives in improving their quality of life and creating sustainable business opportunities. The methodology used includes observation, interviews, and direct implementation of the budikdamber program in the field. The results of this service showed that most of the participants managed to maintain the survival of their fish, although there were some technical constraints such as the quality of the cultivation container and the frequency of feeding that affected the harvest. The program succeeded in improving the knowledge and skills of housewives in fish and plant farming, although there is a need for continuous improvement and monitoring to achieve more optimal results.